Transformasi Tradisi Jawa dalam Seni Grafis Kontemporer: Telaah Karya Cukil Lino Sukamto “Batara Kala Lahir” - Deny Rusanto; Tri Aru Wiratno; Walid Syarthowi Basmalah (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This article examines the transformation of Javanese tradition and mythology into a contemporary visual language through Sukamto’s relief print Batara Kala Lahir (1991). The study applies an art-based research approach using secondary data, including visual documentation, exhibition catalogues, and academic writings on Sukamto’s linocut practice. The analysis combines Susanne K. Langer’s symbolic theory, Feldman’s model of art criticism, and Panofsky’s iconological reading to identify formal elements, interpret symbolic meaning, and compare the work with classical wayang conventions. The findings show that the transformation occurs through three main strategies: deformation of wayang figures, substitution of traditional attributes with modern symbols, and reorganization of mythological narration into social critique. The sharp black-and-white linocut technique strengthens the tension between tradition and modernity, while symbols such as the firearm, skull, heart icon, and hammer-and-sickle tattoo reposition Batara Kala as an allegory of time, destruction, ideology, and moral crisis. The article argues that Sukamto’s work does not merely reproduce Javanese mythology but reactivates it as a critical visual discourse within Indonesian contemporary printmaking. The study contributes to the discussion of tradition-based graphic art by emphasizing iconographic transformation as a strategy for negotiating cultural identity and social reflection.